A revision of the genus Conicofrontia Hampson (Lepidoptera, Noctuidae, Apameini, Sesamiina), with description of a new species: new insights from morphological, ecological and molecular data - (:unkn) unknown (My University, 2015)
The aim of this study was to review the species of Conicofrontia Hampson, a small genus of noctuid stem borers (Noctuidae,Apameini) that is distributed in East and Southeastern Africa. We review the morphology of species in this group and provide new diagnoses and ecological data for five species. The following taxonomic changes are proposed: Hygrostola dallolmoi (Berio, 1973) (= Conicofrontia dallolmoi Berio, 1973) comb. n. and Conicofrontia bipartita (Hampson, 1910) (= Phragmatiphila bipartita Hampson, 1910) comb. n., stat. rev. One new species is also described: C. lilomwa, sp. n. from Tanzania. Wing patterns as well as male and female genitalia of the five species are described and illustrated. Finally we carried out molecular phylogenetic and molecular species delimitation analyses on a multi-marker dataset of 31 specimens and 15 species, including the five mentioned species. The results of molecular analyses provide a clear support for the proposed taxonomical changes.
Keywords: African Research